Two dimensional N $$ \mathcal{N} $$ = (0, 4) quivers dual to AdS3 solutions in massive IIA - Yolanda Lozano; Niall T. Macpherson; Carlos Nunez; Anayeli Ramirez (Journal of High Energy Physics)
Abstract In this paper we discuss an infinite family of new solutions in massive Type IIA supergravity with AdS3×S2 factors, preserving N $$ \mathcal{N} $$ = (0, 4) SUSY. After studying geometrical aspects of the backgrounds we propose a duality with a precise family of quivers that flow to (0,4) fixed points at low energies. These quivers consist on two families of (4,4) linear quivers coupled by matter fields. We present various tests of our proposal.